Community assembly and network structure of epiphytic and endophytic phyllosphere fungi in a subtropical mangrove ecosystem - Zhu, Chunchao; Lin, Yumiao; Wang, Zihui; Luo, Wenqi; Zhang, Yonghua; Chu, Chengjin (Frontiers in Microbiology, 2023)
Microorganisms can influence plant growth and health, ecosystem functioning, and stability. Community and network structures of mangrove phyllosphere fungi have rarely been studied although mangroves have very important ecological and economical values. Here, we used high throughput sequencing of the internal transcribed spacer 2 (ITS2) to assess epiphytic and endophytic phyllosphere fungal communities of six true mangrove species and five mangrove associates. Totally, we obtained 1391 fungal operational taxonomic units (OTUs), including 596 specific epiphytic fungi, 600 specific endophytic fungi, and 195 shared fungi. The richness and community composition differed significantly for epiphytes and endophytes. Phylogeny of the host plant had a significant constraint on epiphytes but not endophytes. Network analyses showed that plant–epiphyte and plant–endophyte networks exhibited strong specialization and modularity but low connectance and anti-nestedness. Compared to plant–endophyte network, plant–epiphyte network showed stronger specialization, modularity, and robustness but lower connectance and anti-nestedness. These differences in community and network structures of epiphytes and endophytes may be caused by spatial niche partitioning, indicating their underlying ecological and environmental drivers are inconsistent. We highlight the important role of plant phylogeny in the assembly of epiphytic but not endophytic fungal communities in mangrove ecosystems.